195 Ultrasound Characterisation of the Murine Myocardium Reveals Dynamic Modification in the Early Post-natal Period. (31st May 2014) - Castellan, Raphael; Thomson, Adrian; Moran, Carmel; Gray, Gillian
Abstract : The neonatal murine heart has been shown to retain a capacity for regeneration following injury until 7 days after birth, after which injury is followed by scar formation (Porello et al ., 2011). However normal physiology and growth characteristics of the heart are poorly defined during this neonatal period. The present study aimed to characterise changes in structure and function of the myocardium during early post-natal growth. Isofluorane anaesthetised mice underwent investigation by 'b mode' and Doppler high resolution ultrasound (Visualsonics Vevo 770) at E18.5, 2 days, 4 days, 8 days, 3 weeks and 6 weeks after birth (n = 5–6 per time-point). ECG and temperature were measured throughout assessment. Hearts were then collected, weighed before fixation and paraffin embedding for wheat-germ agglutinin (WGA) and isolectin B4 staining formeasurement of cardiomyocyte cross sectional area (CM-CSA) and blood vessel density. Left ventricular (LV) wall thickness increased from 440 ± 28 mm to 563 ± 16 mm between 2 and 8 post-partum, without a significant increase in CM-CSA, consistent with a phase of CM hyperplasia, rather than hypertrophy. In contrast, the rate of increase in CM-CSA was significantly greater from 8 days after birth, although not accompanied by a further increase in wall thickness until 3 weeks post-partum, consistent with rearrangement of cardiomyocytes to contribute to increased LV end-diastolic and end-systolic area. Throughout this period function, defined by ejection fraction and by myocardial performance index, remained largely stable. The period between 2 and 8 days after birth was also characterised by a reversal in the ratio of E and A waves in the mitral valve Doppler trace from a foetal-like pattern (0.72 ± 0.07) to an adult-like one (1.28 ± 0.04), consistent with maturation of LV filling. Isolectin B4 staining revealed the presence of large diameter vessels at birth, which reduced in size and became more organised towards 6 weeks post-partum. These data provide the first ultrasound characterisation of myocardial structure function during early post-natal growth. They reveal a pattern of myocardial growth that is consistent with a shift from reliance on proliferation early after birth to hypertrophy and realignment of myocytes from 8 days post-partum. This work is supported by a BHF 4 year PhD studentship to RC and by a BHF Centre of Research Excellence Award. Reference: Porrello ER, et al . Transient regenerative potential of the neonatal mouse heart. Science. 2011;331:1078–1080